Differential effects of alkaloids on sodium currents of isolated single skeletal muscle fibers - Körper, Sixten; Wink, Michael; Fink, Rainer (FEBS letters, 1998)
The effects of the alkaloids ajmaline, lupanine, sparteine, serpentine, strychnine, and yohimbine were studied with the loose patch clamp technique on sodium currents of isolated single skeletal muscle fibers. The IC50 values for half-maximal blocking of the sodium currents were 6.6 μM for ajmaline, 55.7 μM for quinidine, 168.8 μM for sparteine, and 1.2 mM for lupanine. The observed Na+ channel inhibition is in accordance with the use of ajmaline, quinidine and sparteine as antiarrhythmic drugs. The interference of alkaloids with Na+ channels can also be interpreted as a means to strongly interfere with neuronal transmission in herbivores. Alkaloids thus serve as chemical defense compounds for the plants producing them.